Risk factors of local recurrence following implant-based breast reconstruction in breast cancer patients - Miwa Fujihara; Rie Yamasaki; Mitsuya Ito; Tadahiko Shien; Reina Maeda; Takanori Kin; Ayako Ueno; Yukiko Kajiwara; Kensuke Kawasaki; Kouichi Ichimura; Hiroya Mihara; Naritaka Kimura; et al. (BMC, 2021)
Abstract Background The number of patients desiring implant-based breast reconstruction has been increasing. While local recurrence is observed in patients with breast reconstruction, only a few reports have focused on the risk factors for local recurrence and the prognosis after developing local recurrence. Methods We analyzed 387 patients who underwent implant-based breast reconstruction during the period from 2004 to 2017 in Hiroshima City Hospital. We retrospectively examined the risk factors for local recurrence and the outcomes of patients developing such recurrence after implant-based breast reconstruction. Results The median follow-up time was 59 months. The local recurrence rate was 3.1% (n = 12). The most common reason for detecting local recurrence was a palpable mass. Four patients with local recurrence had recurrence involving the skin just above the primary lesion and needle biopsy tract. All patients with local recurrence received surgery and systemic therapy and most patients received radiation therapy, all have remained free of new recurrence to date. Multivariate analysis showed lymphatic vessel invasion (HR, 6.63; 95% CI, 1.40-31.36; p = 0.017) and positive or < 2 mm vertical margin (HR, 9.72; 95%CI, 1.23-77.13; p = 0.047) to be associated with significantly increased risk of local recurrence. Conclusions The risk factors for local recurrence following implant-based breast reconstruction were lymphatic vessel invasion and positive or < 2 mm vertical margin. Removal of the skin just above the primary lesion and needle biopsy tract and adjuvant radiation therapy might improve local outcomes. Patients with local recurrence following implant-based breast reconstruction appear to have good outcomes with appropriate treatment.